(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
The study was assessed to determine the effects of rural-urban youth migration on farm families in Benue state, Nigeria during November 2014 to June 2015. Interview schedule was used to collect data from a sample of 80 respondents. Data were analyzed using frequency, percentage, mean scores and standard deviation. Results indicate that majority (76.3%) of the respondents were males, middle aged and married. Major causes of ruralurban youth migration indicated by the respondents include inadequate employment opportunities in rural areas (M=3.6), search for better education (M=3.5), inadequate social infrastructure such as schools (M=3.4), poor medical care services in rural areas (M=3.4), looking for money through labour (M=3.4), apprenticeship programme (M=3.2), etc. Findings of the study also indicate that reduction of agricultural labour force (M=3.5), low agricultural productivity (M=3.3), high cost of labour (M= 3.3), reduction on demand for locally grown foods (M=2.9), decrease in dependency ratio in the rural areas (M=2.7), reduction on number of mouths to feed (M=2.7), among others were major effects of ruralurban youth migration among farm families. The study recommends that Nigerian government should provide adequate physical and social infrastructure in rural areas in order to encourage youths to remain in agriculture, reduce rural-urban youth migration as well as sustain agriculture for enhanced food security. Int. J. Agril. Res. Innov. & Tech. 6 (1): 14-20, June, 2016